Blunted growth hormone and prolactin responses to L-tryptophan in depression; a state-dependent abnormality. - Upadhyaya, A; Pennell, I; Cowen, P; Deakin, J (1991)
We have investigated whether attenuated growth hormone (GH) and prolactin (PRL) responses to L-tryptophan in depression return to normal with clinical recovery. Ten patients who had received intravenous infusions of L-tryptophan (100 mg/kg) when depressed were retested at least 3 months after full recovery and cessation of treatment. In recovered depressives growth hormone responses showed considerable recovery, in all but three cases to within a few units of their healthy age- and sex-matched controls. Prolactin responses increased with clinical recovery in all six male subjects. Results in females were inconclusive because of the effect of weight loss on prolactin responses. The results suggest that GH and PRL responses to tryptophan are state-dependent abnormalities rather than indicators of predisposition to depression. This allows the possibility that impaired functioning in systems with a 5HT1A or 5HT1D receptor link may be part of the causal chain in depression.